Mobile health technology in providing maternal health services - Awareness and challenges faced by pregnant women in upper West region of Ghana - E. Bekyieriya; S. Isang; B. Baguune (Elsevier, 2023)
Objectives: The study assessed awareness on Mobile Health (mhealth) Technology as well as challenges pregnant women encounter in the utilization of mhealth technology to improve maternal health in rural settings in the Upper West Region (UWR) of Ghana. Study design: The study was an exploratory design that employed the qualitative method of data collection. Methods: Semi-structured interview guide was used to conduct six (6) Focus Group Discussions (FGDs) and nine (9) Key Informant Interviews (KIIs) among pregnant women and health workers respectively from three (3) selected rural districts in the Upper West Region. Data was collected in August 2020. Thematic analysis was conducted and some statements from participants were presented verbatim to illustrate the themes realized. Results: Participants were aware of the mhealth intervention that had been implemented by Savanna Signatures in their districts. Major sources of information on the mhealth services were from durbars, health education sessions and health care providers. Challenges faced by pregnant women, in the mhealth technology intervention were; financial challenges, lack of mobile network connectivity, lack of electricity in some rural areas, low female literacy rate at household level and cultural barriers. Conclusion: The Savanna Signatures mhealth intervention is widely known but some challenges exist that impede the smooth implementation of the intervention. The mhealth technology intervention implementers should partner with other sectors and policy makers to address the challenges identified by the study.